2018
DOI: 10.3208/jgs.13.61
|View full text |Cite
|
Sign up to set email alerts
|

Application for Surface-Wave Method to property of embankment

Abstract: In this paper, we investigate the relationship between S wave velocity distribution and dry density immediately after completion of two test embankments constructed by changing degree of compaction. In addition, we compare the change of S-wave velocity distribution before and after the rainfall, and examined the applicability of surface wave exploration to the change of the properties inside the embankment. As a result, the distribution of the dry density and the S wave velocity distribution obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Figure 12 shows the status of the survey lines for the surface-wave method performed on the levee crown of the reinforced embankment. Kawajiri et al [8] reports that the difference in dry density can be evaluated by the S-wave velocity obtained from the surface-wave method in test embankments with different D c . In addition, it has been reported that the S-wave velocity obtained from the surface-wave method locally decreases in the geosynthetics reinforced soil wall where the deformation occurred [9,10].…”
Section: Changes In Strain Gauges and Earth Pressure Gaugesmentioning
confidence: 99%
“…Figure 12 shows the status of the survey lines for the surface-wave method performed on the levee crown of the reinforced embankment. Kawajiri et al [8] reports that the difference in dry density can be evaluated by the S-wave velocity obtained from the surface-wave method in test embankments with different D c . In addition, it has been reported that the S-wave velocity obtained from the surface-wave method locally decreases in the geosynthetics reinforced soil wall where the deformation occurred [9,10].…”
Section: Changes In Strain Gauges and Earth Pressure Gaugesmentioning
confidence: 99%